Nitrite and Nitrate in Human Health and Disease - Bryan, Nathan S.; Loscalzo, Joseph (Springer International Publishing : Imprint: Humana Press, 2017)
This fully revised and updated new edition provides a comprehensive look at nitrite and nitrate and their effect on human health and disease. The first section describes the biochemical analysis of nitrite and nitrate and its role in human physiology. The book then shifts to sources of human exposure of nitrite and nitrate, including environmental and dietary. Finally, the last section discusses nitric oxide-based therapeutics and how nitrite and nitrate biochemistry can be safely harnessed to improve human health. Each chapter provides a balanced, evidence-based view and heavily cites the most recent published literature. They follow a strict chapter format which includes keywords, key points, a conclusion highlighting major findings, and extensive references. The second edition contains new chapters on nitrite and nitrate in age medicine, nitrite and nitrate as a treatment for hypertension, and nitrite and nitrate in exercise performance. Additionally, the editors have expanded the biochemistry section to include chapters on nitrate reducing oral bacteria, nitrite mediated S-Nitrosation, epigenetics and the regulation of nitric oxide, and nitrite control of mitochondrial function. Nitrate and Nitrite in Human Health and Disease, 2e, will be of interest to health professionals, nutritionists, dieticians, biomedical scientists, and food scientists.
Keywords: Medicine.; Clinical nutrition.; Medical biochemistry.; Ecotoxicology.; elektronické knihy; electronic books